Grupo de autocuidado em hanseníase: benefícios na participação e resistências na adesão. - de Oliveira Barbosa, Samara; Santos Medina, Flávia (Revista de Atencao Primaria a Saude)
Objectives: To describe the limitation of activities and social participation of individuals with leprosy before and after joining a self-care group, to analyze the benefits of the group and non-adherence. Methods: Descriptive and exploratory research with quantitative-qualitative approach with 18 patients undergoing treatment for leprosy, attended and followed up at a health center in Palmas - Tocantins. Data were collected from March to December 2018 through the Identification Questionnaire, SALSA Scales and Social Participation, and Semistructured Interview. The data were analyzed by the Statistical Package for Social Sciences (SPSS) Program and the interviews were conducted through Content Analysis by the categorical analysis technique. Results: Although adherence to the self-care group was low, the participation in it contributed to a reduction in the scores of the Salsa and Social Participation scales and provided patients with knowledge about the disease, knowledge exchange, socialization, improvement of autonomy, self-care and emotional factors. Conclusion: Patient's limitation of activities and social participation may be impaired by leprosy, however, the self-care group helps them to better deal with the disease.